The Chemoselective Reduction of Isoxazoline γ-Lactams Through Iminium Aza-Diels-Alder Reactions: A Short-Cut Synthesis of Aminols as Valuable Intermediates towards Nucleoside Derivatives - Misal Giuseppe Memeo; Mariella Mella; Paolo Quadrelli (The Scientific World Journal)
Isoxazoline γ-lactams are prepared starting from the regioisomeric cycloadducts of benzonitrile oxide to the N-alkyl 2-azanorbornenes taking advantage of the efficient catalytic oxidation by RuO4. The reduction of the amide groups is easily conducted in the presence of LiAlH4 under mild conditions, which allowed for the chemoselective reduction of the amide moiety followed by ring opening to afford the desired conformationally locked isoxazoline-carbocyclic aminols, as valuable intermediates for nucleoside synthesis.